Home Monitoring System by Using Iot - Abdalla Hassan Abakar Eisa,; Radiah Mohamad, (Applied Information Technology And Computer Science, 2023)
Technology is a massive and rapidly expanding process. Home monitoring systems that use IoT are becoming increasingly popular among academics and developers in the modern era. This is related to human nature's desire for a comfortable living. One of the most crucial parts of making life comfortable and feeling secure and peaceful is safety. This project is being developed to assist humans in achieving this feeling. In this home surveillance system, Raspberry Pi is used to integrate sensors, camera, and networks. It applies the concept Internet of Things (IoT) in its system. The main purpose of this project is to observe home more easily and ensure the safety of life and property. In this system, a camera is used to identify intruder outside the home.